Supply chain innovation and performance of manufacturing companies in Nigeria - Barau, Singhry Hassan (2015)
Supply chain management (SCM) is an important strategy for firm competitiveness and performance. Yet issues emerging issues from disparity in technological capability, low level of trust-entwined collaboration, new supply chain capability, top management commitment, supply chain vision and planning, and poor visibility continue to challenge firms’ abilities to deliver quality products at the right cost, place and time. However, literature on supply chain innovation is quite scarce and researchers have lamented that studies in supply chain management have either ignored innovation or innovation itself has overlooked supply chain. Therefore, the need to advance the literature of supply chain innovation through a post-positivism world-view is required more than ever. The general objective of the study was to investigate the relationship between supply chain innovation and supply chain performance from the intervening role of innovation capability and the interactive effect of top management support. Theorizing from the dynamic capabilities theory, social exchange theory, and upper echelon theory, the study postulated a mediated-moderated hypotheses based on the post-positivism worldview. The study was based on cross-sectional survey of 286 manufacturing companies in Nigeria. Cluster and stratified random sampling were employed and self-administered (face-to-face) questionnaires were distributed to the selected companies with help of research assistants. Data was analyze using structural equation modeling with Amos graphics. The findings suggest that supply chain innovation has significant relationship with supply chain performance. Analyses of the indicators of supply chain innovation show that both supply chain technology and supply chain collaboration have significant relationship with supply chain performance. It is also found that supply chain innovation capability is significantly related with supply chain performance. Further analyses of mediation indicates that supply chain innovation capability is a full mediator between on relationship between supply chain technology and supply chain performance as well as on relationship between supply chain collaboration and supply chain performance. The findings also provided evidence of partial moderating effect of top management support on the relationship between supply chain technology and supply chain performance. However, top management support does not moderate the relationship between supply chain collaboration and supply chain performance. The study enhances literature of supply chain innovation by advancing theoretical knowledge and empirical evidence of how indicators of supply chain innovation through supply chain technology and supply chain collaboration could be integrated with managerial roles and innovation capability to improve supply chain performance. For practice, the study provides guidance to managers to design innovative supply chain. Limitations and recommendations for further studies are provided.